Military-government relationships in environmental justice protections: a Colorado case study - Haberlack, Emily, author; Malin, Stephanie, advisor; Mao, KuoRay, committee member; Harris, Peter, committee member (Colorado State University. Libraries, 2024)
This thesis aims to examine the environmental and public health experiences of individuals who worked and live(d) in El Paso County, Colorado, during and after the public was informed of high levels of per – and polyfluoroalkyl substances (PFAS) chemical contamination in the Fountain Valley local drinking water from Air Force military activity on Peterson Air Force Base in 2016. I've collected the data presented in this thesis to study the dynamics between mobilized community members, local government, and military as they navigate the environmental justice issues of contested illness, community safety, and harm from military activity in the United States. The data collected includes qualitative interviews from community members and personnel who were involved in protecting residents and providing safe drinking water. In addition, I conducted content analysis on news reporting of the water contamination to investigate how information on the hazard was communicated to the public. The U.S. military is the largest polluting entity in the world (Woodward, 2004; LaDuke & Cruz, 2013). As such, the military-industrial complex is responsible for environmental contamination and harms across the country and within the communities they occupy (Woodward, 2004). PFAS chemicals are contaminants that enter the environment and human bodies through production, distribution, and waste processes from the companies that create them and industries that use them, like the military and firefighters. PFAS are historically found in aqueous film-forming foam (AFFF), a fire suppressant that was created by 3M and the U.S. military and ubiquitously used on military bases since the 1970s. These activities have spread the chemical compounds throughout urban and rural spaces and have created massive implications for the health and safety of community drinking water sources. These chemicals are identified as "forever chemicals" due to their strong chemical bonds which do not easily break down in the environment and have been shown to bioaccumulate in the human body. As an emergent contaminant1, PFAS exposure is highly contentious, and studies are still being conducted to concretely link exposure to detrimental health effects like thyroid issues and cancers. The research that has been completed has identified PFAS as having concerning health effects for human health (Mueller et al., 2024; Cordner et al., 2021). As such, communities exposed to PFAS contamination face unique challenges pursuing environmental justice, defined as the equitable distribution of environmental benefits and burdens, ensuring that all communities, particularly marginalized ones, have equal access to a clean and healthy environment, and are not disproportionately affected by environmental harms. (Roberts et al., 2018). This research utilizes the concepts of distributive and procedural justice, and contested illness from the environmental justice literature. These environmental justice concepts are combined with the treadmill of destruction theory to study community relationships and dynamics after military created PFAS water contamination in the Fountain Valley. Findings from my thesis show how the Fountain Valley community members' struggles for clean water and for recognition of their health impacts from PFAS exposure illustrate a broader issue of positional power dynamics. Affected residents, often left out of key decision-making processes, faced significant barriers to accessing meaningful and useful, translated information about the risks they faced. The Air Force's financial contributions to water filtration efforts, while necessary, do not absolve the institution of responsibility for the long-term health and social impacts of contamination they caused—responsibility they have not fully claimed, while also avoiding authentic communication with the communities and people their actions affected. Instead, the true leaders in this environmental crisis have been mobilized community members, who have fought tirelessly for procedural justice and greater transparency in the face of systemic failures. Understanding the lived, psycho-social experiences of communities and local government as they navigate contested illness and public infrastructure safety after military contamination is critical to questions of justice and environmental contamination surrounding the leading global polluter, the U.S. military.
Keywords: embodied health social movements; procedural justice; water contamination; PFAS; contested illness; slow violence